2023
DOI: 10.1101/2023.12.20.572426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking SARS-CoV-2 variants of concern in wastewater: an assessment of nine computational tools using simulated genomic data

Steven G. Sutcliffe,
Susanne A. Kraemer,
Isaac Ellmen
et al.

Abstract: Wastewater-based surveillance (WBS) is an important epidemiological and public health tool for tracking pathogens across the scale of a building, neighbourhood, city, or region. WBS gained widespread adoption globally during the SARS-CoV-2 pandemic for estimating community infection levels by qPCR. Sequencing pathogen genes or genomes from wastewater adds information about pathogen genetic diversity which can be used to identify viral lineages (including variants of concern) that are circulating in a local pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The result is that each initial detection, even if isolated, should be treated as valuable data if it is going to serve as an early warning signal.It is not typical to place con dence in single detections from WW surveillance due to the nature of the sample type, being comprised of many different individual viral particles and with each particle contributing a partially degraded genome, necessitating frequency prediction tools to 'detangle' the sample into individual lineages and there are limits to the accuracy of such tools. For example, a benchmarking publication which included Alcov concluded that calls at frequencies less than 5% should be interpreted with caution due to high background noise in WW samples(Sutcliffe et al, 2023). As a result, in municipal WW surveillance patterns and trends in data especially in slowly emerging lineages lend con dence to the predictions.…”
mentioning
confidence: 99%
“…The result is that each initial detection, even if isolated, should be treated as valuable data if it is going to serve as an early warning signal.It is not typical to place con dence in single detections from WW surveillance due to the nature of the sample type, being comprised of many different individual viral particles and with each particle contributing a partially degraded genome, necessitating frequency prediction tools to 'detangle' the sample into individual lineages and there are limits to the accuracy of such tools. For example, a benchmarking publication which included Alcov concluded that calls at frequencies less than 5% should be interpreted with caution due to high background noise in WW samples(Sutcliffe et al, 2023). As a result, in municipal WW surveillance patterns and trends in data especially in slowly emerging lineages lend con dence to the predictions.…”
mentioning
confidence: 99%